Experimental Investigation on Shear Strength and Liquefaction Potential of Rubber-Sand Mixtures - Zhou Enquan; Wang Qiong (Advances in Civil Engineering)
The application of scrap tires as construction materials in civil engineering is one of the most promising ways to recycle this pollutant. The objective of this study was to investigate the shear strength and liquefaction potential of saturated rubber-sand mixtures. Direct shear tests and cyclic triaxial tests were conducted on rubber-sand mixtures at various rubber contents. It was found that the addition of rubber particles to sand changed the shear stress-horizontal displacement development. The addition of rubber particles to sand improved the shear strength slightly and improved resistance to liquefaction significantly. Additionally, a hyperbolic model was proposed to describe the pore water pressure generation. This study demonstrates the effect of rubber particles on the physical properties of sand.